Effectiveness of The Implementation of The Extension Program for Rice Farming in Suranenggala Kidul Village, Suranenggala District, Cirebon Regency - Sutandi, Sutandi; Firmansyah, Adi; Ruhadi, Ruhadi; Faqih, Achmad; Aisyah , Siti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study was to determine the process of planning and implementation of the Rice paddy farming extension program and to evaluate the effectiveness of the extension program. The methods and type of research used descriptive quantitative methods with survey techniques and a sample size of 40 rice farmers. The results showed: (1) The planning and implementation of extension programs in Suranenggala Kidul Village, Suranenggala District, Cirebon Regency involved two planning processes, namely the involvement of farmers in planning the extension programs and their involvement in decision-making, with an average score of 2.5. Meanwhile, for the implementation of extension programs, there were eight components with an average score of 2.71; and (2) The effectiveness of the planning and implementation of the extension program for paddy rice in Suranenggala Kidul Village, Suranenggala District, Cirebon Regency is categorized as effective. This is evidenced by farmer participation, timely implementation of extension programs, alignment of the programs with farmers' needs, appropriate duration, implementation according to targets, increased production, changes in the level of adoption by farmers, and the level of farmer satisfaction.